The IRHUM (Isotopic Reconstruction of Human Migration) database – bioavailable strontium isotope ratios for geochemical fingerprinting in France - M. Willmes; L. McMorrow; L. Kinsley; R. Armstrong; M. Aubert; S. Eggins; C. Falguères; B. Maureille; I. Moffat; R. Grün (Earth System Science Data, 2014)
Strontium isotope ratios (87Sr / 86Sr) are a key geochemical tracer used in a wide range of fields including archaeology, ecology, food and forensic sciences. These applications are based on the principle that the Sr isotopic ratios of natural materials reflect the sources of strontium available during their formation. A major constraint for current studies is the lack of robust reference maps to evaluate the source of strontium isotope ratios measured in the samples. Here we provide a new data set of bioavailable Sr isotope ratios for the major geologic units of France, based on plant and soil samples (Pangaea data repository doi:10.1594/PANGAEA.819142). The IRHUM (Isotopic Reconstruction of Human Migration) database is a web platform to access, explore and map our data set. The database provides the spatial context and metadata for each sample, allowing the user to evaluate the suitability of the sample for their specific study. In addition, it allows users to upload and share their own data sets and data products, which will enhance collaboration across the different research fields. This article describes the sampling and analytical methods used to generate the data set and how to use and access the data set through the IRHUM database. Any interpretation of the isotope data set is outside the scope of this publication.